2013
DOI: 10.1186/2196-1042-14-21
|View full text |Cite
|
Sign up to set email alerts
|

Mini-implants and the efficiency of Herbst treatment: a preliminary study

Abstract: BackgroundThe purpose of this study is to present the use of a modified Herbst appliance in association with temporary anchorage devices (TADs) in order to enhance the correction of skeletal class II malocclusions.MethodsTen consecutive adolescents scheduled for Herbst treatment were assigned to two treatment groups. Five cases were treated with a modified miniscrew-supported Herbst appliance (experimental group (EG)) and five cases with a conventional cast Herbst appliance (control group (CG)). In all cases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 20 publications
0
23
1
1
Order By: Relevance
“…Those studies have proven the efficiency of fixed functional appliances; however, protrusion of mandibular incisors was also reported to be a common finding that limits the skeletal effects of the appliance used. 16,17 The use of miniscrew and miniplate anchorage in orthodontics has reduced the undesirable effects of many appliances. [18][19][20][21] Few studies 16,17,22,23 have shown the use of the Herbst and Forsus Fatigue Resistant Device (FRD) with miniscrew anchorage.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Those studies have proven the efficiency of fixed functional appliances; however, protrusion of mandibular incisors was also reported to be a common finding that limits the skeletal effects of the appliance used. 16,17 The use of miniscrew and miniplate anchorage in orthodontics has reduced the undesirable effects of many appliances. [18][19][20][21] Few studies 16,17,22,23 have shown the use of the Herbst and Forsus Fatigue Resistant Device (FRD) with miniscrew anchorage.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 The use of miniscrew and miniplate anchorage in orthodontics has reduced the undesirable effects of many appliances. [18][19][20][21] Few studies 16,17,22,23 have shown the use of the Herbst and Forsus Fatigue Resistant Device (FRD) with miniscrew anchorage. Those studies 16,22,23 have shown that the skeletal response to the Herbst appliance was increased by minimizing the protrusion of the mandibular incisors, while the overjet and molar correction in patients treated with the Forsus FRD combined with miniscrew anchorage were totally dentoalveolar.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zur Minimierung unerwünschter Nebenwirkungen gewinnen in der modernen Kieferorthopädie zunehmend kortikale Verankerungssysteme an Bedeutung. Diese Verankerungsschrauben bieten erstmals eine Methode der Verankerung, ohne reziproke Kräfte auf andere dentale Einheiten zu übertragen [8]. Die hier vorgestellte Methode soll die Möglichkeiten der modernen Kieferorthopädie am Beispiel einer Erwachsenenbehandlung ohne kieferchirurgische Umstellungsosteotomie im Sinne einer Camouflage-Behandlung aufzeigen.…”
unclassified
“…8 Many studies have proven the efficiency of Herbst for the treatment of Class II malocclusion [9][10][11][12] , however, some authors have attributed several side effects to the use of functional appliances -eg, protrusion of mandibular incisors. 8,13 Nowadays, the Forsus Fatigue Resistant device (3M Unitek, Monrovia, California) is a new fixed semirigid system, where its producer guarantees to be resistant against fractures and external forces. 14 The FRD is a threepiece, semirigid telescoping system incorporating a superelastic nickel-titanium coil spring that can be assembled chair-side in a relatively short amount of time.…”
Section: Introductionmentioning
confidence: 99%